2010
DOI: 10.1080/10934529.2010.513262
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in drinking water wells on the Bolivian high plain: Field monitoring and effect of salinity on removal efficiency of iron-oxides-containing filters

Abstract: Arsenic in drinking water wells on the Bolivian high plain: Field monitoring and effect of salinity on removal efficiency of iron-oxides containing filters K. VAN Synthetic drinking water could be treated effectively by the IOCS and CIM based filters reducing As to concentrations lower than 10 µg L -1 . High levels of chloride and sulphate did not influence As removal efficiency. However, phosphate concentrations in the range from 4 to 24 mg L -1 drastically decreased removal efficiency of the IOCS based fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the South American continent, >1 cm/year subsidence has been mapped over small, irrigated regions in Argentina and Peru. In Bolivia, >5 cm/year subsidence has been predicted over groundwater dependent cities 44 , 45 of Oruro and Cochabamba.…”
Section: Resultsmentioning
confidence: 99%
“…In the South American continent, >1 cm/year subsidence has been mapped over small, irrigated regions in Argentina and Peru. In Bolivia, >5 cm/year subsidence has been predicted over groundwater dependent cities 44 , 45 of Oruro and Cochabamba.…”
Section: Resultsmentioning
confidence: 99%
“…The second step in the process is the interaction between HFO and the As species. Arsenic adsorption on iron oxide phases varies with pH, As speciation, initial As concentration, and As/Fe ratio. Numerous studies have demonstrated the robustness and greater ease of As­(V) removal (relative to As­(III)) by iron oxide adsorption under a wide range of conditions and solution pH. For this reason, we have focused our preliminary investigation of pH dependence of our system on the As­(III) species; our findings are discussed when the Jar test experiments are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Considering this, some researchers have applied commercial iron-nails in different water/ wastewater treatments e.g. in sand filters during the filtration process for arsenic removal [38][39][40][41], in Electrocoagulation process for removal of mercury (II) [42], and in ultrasound-assisted Fenton process for wastewater treatment [43]. However, the application of commercial iron-nails for NOM removal in the drinking water treatment plants has not been reported.…”
Section: Introductionmentioning
confidence: 99%